2017
DOI: 10.1016/j.rse.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Driving forces of recent vegetation changes in the Sahel: Lessons learned from regional and local level analyses

Abstract: A wide range of environmental and societal issues such as food security policy implementation requires accurate information on biomass productivity and its underlying drivers at both regional and local scales. While many studies in West Africa are conducted with coarse resolution earth observation data, few have tried to relate vegetation trends to explanatory factors, as is generally done in land use and land cover change (LULCC) studies at finer scales. In this study we proposed to make a bridge between vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
99
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(126 citation statements)
references
References 90 publications
12
99
0
1
Order By: Relevance
“…between geographic variables described above, these linear hypotheses usually lead to biased results. Second, previous research commonly explored the relationships between vegetation growth and climatic factors from a time series, ignoring their spatial differences [26][27][28][29][30]. Thirdly, previous studies have not quantitatively assessed the interaction between two or multiple factors, which are commonly used to quantitatively check whether two or multiple environmental determinants work independently or not.…”
Section: Introductionmentioning
confidence: 99%
“…between geographic variables described above, these linear hypotheses usually lead to biased results. Second, previous research commonly explored the relationships between vegetation growth and climatic factors from a time series, ignoring their spatial differences [26][27][28][29][30]. Thirdly, previous studies have not quantitatively assessed the interaction between two or multiple factors, which are commonly used to quantitatively check whether two or multiple environmental determinants work independently or not.…”
Section: Introductionmentioning
confidence: 99%
“…To explore the underlying drivers of the changes in WUE, we selected the main driver by analyzing the importance of every factor to the WUE. Here, we calculated the variable importance with the internal importance measurement of the random forest (RF) algorithm to identify the drivers with the most important contributions to changing trends in the WUE [57]. The RF is an effective algorithm for optimizing learning accuracy without obviously complicating the calculation [58], and it has been widely used in geography and ecology [57,59,60].…”
Section: Analysis Of the Drivers Of The Changes In The Wuementioning
confidence: 99%
“…The WUE trends (WUE-K) were treated as the target variables to be explained. The mean value of the climate factors represented the general climate conditions over a period of time, while the trends of the slope reflected the changes in the climate conditions over many years [57]. One RF model was set up for each of the four regions in this study.…”
Section: Analysis Of the Drivers Of The Changes In The Wuementioning
confidence: 99%
“…The residual analysis method proposed by Evans and Geerken [33] in 2004 was considered to be robust and has been widely accepted to separate the effects of climate change and human activities on vegetation cover change [17]. Based on the residual analysis method, we established the multiple regression models of the NDVI, temperature and precipitation for every pixel in order to obtain the predictive value of the NDVI (NDVI P ), which is regarded as the influence of the climatic factors on the changes in the NDVI.…”
Section: Analysis Of the Respective Effects Of Climate And Humans On mentioning
confidence: 99%
“…For example, Faramarzi et al [16] created the NDVI maps of 1986, 2001, and 2013 to evaluate the vegetation change in a semiarid rangeland in western Iran, and the authors found that the amount of precipitation seemed to be one of the most important factors that affected the vegetation in the study area. Leroux et al [17] successfully combined vegetation trend analysis with land use and land cover change (LULCC) studies to analyze the driving force of the biomass production changes that were represented by the NDVI. Muriithi et al [18] investigated the trends in the average annual NDVI before and after the presumed onset of rapid horticulture in the central highlands of Kenya, and the authors further analyzed the relationship between the average annual NDVI and specific driving factors, such as population density, large-scale commercial farms, and mean annual rainfall in sub-watersheds.…”
mentioning
confidence: 99%